Determinan utang luar negeri Indonesia dengan pendekatan error correction model (ECM) - Rahayu, Yunita Rizqi; Hodijah, Siti; Mustika, Candra (e-Journal Perdagangan Industri dan Moneter, 2022)
Abstract The purpose of this research is: 1) to identify the development of foreign debts, exchange rates, exchange reserves, GDP, imports, and exports in Indonesia. 2) to analyze the long-term and short-term impact of exchange rates, exchange reserves, GDP, imports, and exports on Indonesian foreign debt. This study uses a quantitative descriptive analysis method of time-series data from 1995 to 2019. It uses multiple linear regression analysis tools with the Ordinary Least Square (OLS) and Error Correction Model (ECM) with the help of Eviews 8. The source of data from the Sentral Statistics Agency (BPS) and Bank Indonesia. The data analysis technique is multiple linear regression, unit root test, ECM, partial hypothesis testing using t-test and simultaneously using F-test with a significance level of 5%. Based on the results, it can be concluded that in the long-term, the exchange rate, foreign exchange rate, GDP, imports, and exports have a significant effect on foreign debt, while in the short-term, GDP does not have a significant impact on foreign debt.